Optimizing Safety Riding by the Security and Safety Unit of Traffic Unit Grobogan Resort Police to Realize Security, Safety, Order, and Continuity of Traffic - Dhito, Muhamad (Indonesian Journal of Police Studies, 2024)
The number of traffic accidents in Grobogan Regency in 2022will increase, especially the rise of people who do not care about safety riding, moreover the policy of the National Police leadership prioritizes electronicticketing (ETLE), because of that many people are indifferent totrafficviolations because they have the opportunity not to be ticketedbythepolice . The implementation of Dikmas activities is not in accordancewiththe guidelines so that the community has not been optimally educatedwhich has an impact on the high number of traffic violations andanincrease in the number of traffic accidents. Therefore it is necessarytomake efforts to optimize the safety riding of the Kamsel Unit of theGrobogan Police in order to create Kamseltibcarlantas. This research methodology used is a qualitative research methodwith the type of research in the form of field research. Data collectiontechniques through interviews, observation, and document studies. Thedata analysis method uses an interactive model which consists of datareduction, data presentation, and drawing conclusions. This researchfocuses on optimizing the safety riding of the Kamsel Unit of the GroboganPolice in order to create security, safety, order and smoothtraffic(Kamseltibcarlantas). The concept used is the concept of traffic, the concept of safetyriding, and the concept of traffic accidents. Theories used includeSWOTanalysis theory in the form of strengths, weaknesses, opportunitiesandthreats, management theory with POAC, and organizational resourcetheory in the form of man, money, material, method, machine and market. The formulation of the problem to be solved is the GroboganPolice Satlantas Traffic Unit resources, namely the number of personnel, personnel competence, budget, and infrastructure using the theoryof organizational resources. The solution to the next problemis theworksystem of Dikmas and then the Grobogan Porles Traffic Unit, namelyregarding the absence of leadership directives, wasdal, and evaluationanalysis by solving problems using management theory.